2021
DOI: 10.3390/vaccines9050460
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Predictors of Hesitancy toward SARS-CoV-2 Vaccine among Type 2 Diabetic Patients: Results from an Italian Survey

Abstract: Vaccine hesitancy (VH) has been identified as one of the major health concerns of our time by the World Health Organization. It may prove especially detrimental in the light of the ongoing SARS-CoV-2 pandemic, as vaccination campaigns still represent the primary strategy against the detrimental consequences of the pandemic. Among patients suffering from type 2 diabetes mellitus (DB), who are particularly vulnerable to COVID-19, VH might represent an even more serious threat. Therefore, our study focuses on ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 18 publications
7
44
1
Order By: Relevance
“…Our findings show that males, participants with a higher level of education and younger people (<40 years) were more likely to get a COVID-19 vaccine. As for males, a higher vaccine confidence has already been documented by several studies [ 17 , 18 , 19 , 20 , 21 ], and could be explained by a higher risk perception of COVID-19, which has been shown from the beginning of the pandemic to be particularly severe in this specific population [ 22 ]. Similarly, what was found regarding the level of education corresponds with the current scientific literature, with a higher level of education being a protective factor against VH for COVID-19 vaccines [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our findings show that males, participants with a higher level of education and younger people (<40 years) were more likely to get a COVID-19 vaccine. As for males, a higher vaccine confidence has already been documented by several studies [ 17 , 18 , 19 , 20 , 21 ], and could be explained by a higher risk perception of COVID-19, which has been shown from the beginning of the pandemic to be particularly severe in this specific population [ 22 ]. Similarly, what was found regarding the level of education corresponds with the current scientific literature, with a higher level of education being a protective factor against VH for COVID-19 vaccines [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 92%
“…This could be explained by the fact that younger people, less affected by the disease, possibly see the vaccine as the most rapid and efficient means to return to their normal lives [ 28 ]. In another study, conducted on a representative sample from the Emilia-Romagna region, we found how the relationship between age and vaccine confidence could be described with a U-shape [ 29 ], while in several studies increasing age has been shown to be a protective factor against VH [ 22 , 25 , 30 ], possibly due to a higher reliance on traditional information sources and less exposure to social media [ 31 ]. The difference we found could be explained by the particular settings in which the questionnaires were collected (pharmacies and swab-screening for SARS-CoV-2) and the period in which the study was performed (beginning of the vaccination campaign).…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, there is little to no information regarding the vaccine acceptance rate in the diabetic population. Another study reported 14.2% vaccine hesitancy among type 2 diabetic patients, most of whom were afraid of previous adverse events or denied vaccinating [ 32 ]. Furthermore, rates of reluctance to be vaccinated among patients with diabetes were also seen for influenza vaccination as well [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with comorbidities had a direct decreased risk of vaccine hesitancy, and this could be related to a higher risk perception and awareness of potential severe COVID-19 and poor outcomes among patients affected by chronic disease [44][45][46][47]. Interestingly, they relied both on social media and institutional websites as a source of information on vaccination towards COVID-19, and this could be probably due to a profound need of information in relation to their condition or to a possible higher confidence in official scientific sources because of their frequent contact with healthcare personnel and a possible greater sensitivity to vaccination to protect themselves from the burden of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%